2016
DOI: 10.3390/ijerph13070701
|View full text |Cite
|
Sign up to set email alerts
|

Quality Matters: Systematic Analysis of Endpoints Related to “Cellular Life” in Vitro Data of Radiofrequency Electromagnetic Field Exposure

Abstract: Possible hazardous effects of radiofrequency electromagnetic fields (RF-EMF) at low exposure levels are controversially discussed due to inconsistent study findings. Therefore, the main focus of the present study is to detect if any statistical association exists between RF-EMF and cellular responses, considering cell proliferation and apoptosis endpoints separately and with both combined as a group of “cellular life” to increase the statistical power of the analysis. We searched for publications regarding RF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 117 publications
0
39
1
1
Order By: Relevance
“…While EMFs used in wireless communication devices (wEMF) have been reported to affect various aspects of cell physiology, including the integrity of the genetic material [4][5][6][7][8], the underlying experimental evidence has been a subject of controversy both in the scientific community and in the public. Indeed, the exposure-related effects are often at the borderline of methodological sensitivity and statistical significance and, therefore, challenging to reproduce in independent settings [8,9]. Nevertheless, evidence for an impact of wEMFs on genome integrity should be carefully investigated, as this may indicate a mutagenic potential, which, even if minor, may be associated with an increased risk of cancer or degenerative human diseases.The impact of environmental agents on DNA integrity can be assessed in different ways.…”
mentioning
confidence: 99%
“…While EMFs used in wireless communication devices (wEMF) have been reported to affect various aspects of cell physiology, including the integrity of the genetic material [4][5][6][7][8], the underlying experimental evidence has been a subject of controversy both in the scientific community and in the public. Indeed, the exposure-related effects are often at the borderline of methodological sensitivity and statistical significance and, therefore, challenging to reproduce in independent settings [8,9]. Nevertheless, evidence for an impact of wEMFs on genome integrity should be carefully investigated, as this may indicate a mutagenic potential, which, even if minor, may be associated with an increased risk of cancer or degenerative human diseases.The impact of environmental agents on DNA integrity can be assessed in different ways.…”
mentioning
confidence: 99%
“…Second, "blind" analysis was not mentioned for MN indices. Previous publications have reported that the biological/genetic damage investigations have significantly greater likelihood of reporting (presumably incorrectly) positive effects of RF exposure when positive controls and blind analyses were not included in the experimental protocol (Simko et al, 2016;Vijayalaxmi and Prohoda, 2019). The European Commission's Scientific Committee on Emerging and Newly Identified Health Risks included these as minimum requirements to ensure that the quality of the data that are collected are useful for health risk assessment from RF exposure (SCENIHR, 2015).…”
Section: Methodsological Issuesmentioning
confidence: 99%
“…If in doubt, it can be tested in large-scale animal experiments under controlled exposure conditions to exclude biases and conflicts of interest. The accurate control of the exposure and experimental procedures is crucial [23]. As for the regulations, strictly observed realistic safety norms are more helpful for the public health than excessive restrictions that would be disregarded.…”
Section: Mobile Phones: Carcinogenic and Other Potential Risksmentioning
confidence: 99%
“…However, in view of the lack of verification of any proposed non-thermal interaction mechanism, established knowledge does not suggest RF-EMF effects accumulating with time [22]. In particular, no correlations between exposure duration and cellular responses in vitro were found [23]. People using mobile phones the longest (>10 years) and accumulating the highest lifetime call hours might be expected to have the highest risk.…”
mentioning
confidence: 99%